El dimensionamiento geométrico y su incidencia en la eficiencia energética de la turbina pelton de las unidades tres y cuatro, en la central de generación hidroeléctrica Illuchi i, de la empresa Elepco S.A. elaboración de una base informática de respaldo de ingeniería Cad – Cam. - Toro Rubio, Jaime Patricio (2017)
The present project seeks to obtain maximum efficiency in the Pelton turbine of units three and four of the hydroelectric generation plant Illuchi I in the company ELEPCO S.A., by the appropriate geometric dimensioning in function of the characteristics of the water source. Deficiencies in manufacturing methods and engineering data loss have been identified, resulting in a loss of efficiency system and reduced reliability in the operation of the equipment. It made the simulation of the behavior of the blade in contact with the fluid through of design software, besides; the hydrodynamics with respect to the water circulation by the surface of the piece, to obtain the greater efficiency and decrease the lost characteristics produced by the system. This model besought is based on the identification, evaluation and characterization of the operational parameters, and the reference measurements of the Pelton turbine were determined to be evaluated by simulation software using the finite element method and to obtain an increase in the Power of 230.92 kW per generation unit, resulting in an annual return of US $ 159611.90 and with a price of US $ 0.04 per kWh. In this way the objective of an efficient energy system based on the correct geometric dimensioning, supported by the development of a CAD - CAM digital computer base, is fulfilled.